Engenharia de tecido ósseo a partir da cultura de células-tronco mesenquimais em matriz de quitosana-gelatina: avaliação in vitro e in vivo, em alvéolos dentários de ratos - Suzana Coulaud da Costa Cruz (2010)
The association of stem cells and biomaterials is a promising alternative for bone reconstruction. In the present study, the in vitro and in vivo behavior of the mesenchymal stem cells from rat bone marrow cultured in a chitosan and gelatin tridimensional matrix. This matrix was synthesized and characterized chemical (energy dispersive x-rays - EDS, x-ray diffraction - XRD) and morphologically (light microscopy, scanning electron microscopy and confocal microscopy). Mesenchymal stem cells from bone marrow (BMSC) obtained from Lewis rats transgenic for eGFP (enhanced green fluorescent protein) were seeded in these scaffolds. In vitro and in vivo experiments were performed with mesenchymal stem cells endogenously tagged with eGFP (enhanced green fluorescent protein) from transgenic rat inbred strain Lewis-eGFP positive (University of Missouri - USA) and Wild Type Lewis-eGFP negative rats were, subsequently, used as receptors, to allow monitoring the fate in vivo of the transplanted cells, by immunohistochemical technique. The scaffolds synthesized were also evaluated in vitro for the biocompatibility (MTT conversion, alkaline phosphatase activity and morphological analyzes by SEM and LM) and the cells behavior were compared (colonization, adhesion, proliferation and osteogenic differentiation) in monolayer and in tridimensional cultures maintained in basal medium, Dulbeccos modified Eagles medium (DMEM) and in osteogenic medium (DMEM plus osteogenic supplements). In vivo, thirty-two wild male rats were used as recipients for the implantation of the scaffold (n=16) or for the transplantation of the construct (n=16) and the tooth sockets of rats model were employed. Therefore, after extraction of the first upper molars, the scaffolds/constructs were implanted in the left dental sockets of the recipient rats, Lewis Wild Type. The right dental sockets were used as controls. The animals, Lewis rats (n=16) from each experimental group were euthanized 5, 21 and 35 days after surgery. The behavior, biocompatibility and biodegradation of the matrix after implantation were evaluated histologically by light microscopy, for the three experimental periods. The constructs implants (scaffold seeded with BMSC in basal medium for three days) were also evaluated in the three experimental periods. Morphometric analysis was performed to quantify bone filling of the experimental sockets, left side, and controls, right side, in periods of 5, 21and 35 days after surgery by means of cone beam computed tomography (CBCT). The fate of the eGFP-positive stem cells transplanted was screened by immunohistochemistry. The in vivo results showed high biocompatibility and slow degradation of the matrix. Morphometric analysis showed a significant increase in bone mineralization in the sockets transplanted after 21 and 35 days. Immunohistochemistry revealed the contribution of BMSC to repair bone, epithelial and vascular tissues. The gelatin and chitosan scaffolds showed physic-chemical and biological properties suitable for use as a filling material, as a carrier for stem cells and reconstitution of the bone tissue by means of tissue engineering. The results showed that the gelatin and chitosan scaffold is a promising carrier biomaterial for BMSC and the construct (chitosan and gelatin scaffold-BMSC) represents a viable strategy for bone tissue engineering in dentistry.